Business forecasting : an economic approach - Robinson, Colin (London : Nelson, 1971)
Business forecasting an economic approach coves topics like: the approach to forecasting; the company's forecasting problem; the macro-environment; the market environment; forecasting market share; the methodology of forecasting a general view; techniques in correlation and regression analysis; some problems in applying correlation and regression analysis.
Includes bibliographical references.
lje 12/12/18
Loans
Keywords: Business forecasting; Economic forecasting